Relationship of Physical Activity and Body Mass Index in Employees of UPTD Puskesmas La'o Kelurahan Wali Langke Rembong District - Jeo, Ida Flaviana; Lada, Christina Olly; Deo, Dwita Anastasia; Setianingrum, Elizabeth L.S. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Insufficient physical activity is a major risk factor for obesity, which is a global health problem, including in Indonesia. Community health center employees as health workers have a high risk of becoming obese due to a sedentary lifestyle. This study aims to explore the relationship between physical activity and body mass index (BMI) in UPTD employees of La'o Community Health Center, Wali Village, Langke Rembong District. This research uses design cross-sectional with a sample of 54 health center employees selected randomly purposive sampling. Physical activity data was collected using a questionnaire-based questionnaire Metabolic Equivalent of Task (METs), while BMI is calculated from measurements of weight and height. Data analysis was carried out using the Fisher’s Exact test. Respondents with active physical activity mostly had a normal Body Mass Index (BMI), while respondents with inactive physical activity were more likely to have an abnormal BMI. Overall, 63% of respondents had a normal BMI and 37% had an abnormal BMI, with the proportion of active and inactive respondents each being 50%. The findings from the analysis conducted with Fisher's Exact Test indicated a notable connection between exercise and Body Mass Index, with a p-value of less than 0.001. A clear link exists between exercise and BMI among employees at community health centers. Boosting physical activity can serve as a crucial approach to avoid obesity in healthcare workers.